The Mechanism of Alternating Current Corrosion of API Grade X65 Pipeline Steel - Iannuzzi, Mariano; Ghanbari, E.; Lillard, R. (NACE International, 2016)
In the present work, corrosion rates of API grade X65 pipeline steel in sodium chloride solutions with and without alternating currents (AC) at different direct current (DC) potentials were measured using weight loss analysis. The results show that the effect of AC is most pronounced near the open-circuit potential; at more positive potentials, the rates approach those of the ohmic drop/mass transport-limited DC rates. Correspondingly, at negative potentials the rates decrease. Surprisingly, it was found that at all potentials, the AC corrosion rate was equal to the average AC current in the system. The data generated from weight loss experiments were compared with the results from a model for AC corrosion that was developed using a modified Butler-Volmer approach. The model considers the anodic and cathodic Tafel slopes, diffusion limited oxygen transport, interfacial capacitance, and solution resistance. Both experimental and model results showed the importance of the interfacial capacitance on the rate of AC corrosion, especially at a frequency of 60 Hz. The models were also used to explain the observation that the AC corrosion rate was equal to the average AC current in the system.